Iron-catalyzed trimerization of terminal alkynes enabled by pyrimidinediimine ligands: a regioselective method for the synthesis of 1,3,5-substituted arenes - Doll, Julianna S.; Eichelmann, Robert; Hertwig, Leif E.; Bender, Thilo; Kohler, Vincenz J.; Bill, Eckhard; Wadepohl, Hubert; Roşca, Dragoş-Adrian (ACS catalysis, 2021)
The development of pyrimidine-based analogues of the well-known pyridinediimine (PDI) iron complexes enables access to a functional-group-tolerant methodology for the catalytic trimerization of terminal aliphatic alkynes. Remarkably, in contrast to established alkyne trimerization protocols, the 1,3,5-substituted arenes are the main reaction products. Preliminary mechanistic investigations suggest that the enhanced π-acidity of the pyrimidine ring, combined with the hemilability of the imine groups coordinated to the iron center, facilitates this transformation. The entry point in the catalytic cycle is an isolable iron dinitrogen complex. The catalytic reaction proceeds via a 1,3-substituted metallacycle, which explains the observed 1,3,5-regioselectivity. Such a metallacycle could be isolated and represents a rare 1,3-substituted ferracycle obtained through alkyne cycloaddition.
Gesehen am 03.03.2022